2017
DOI: 10.18388/abp.2017_1528
|View full text |Cite
|
Sign up to set email alerts
|

Surface structure changes of pathological placenta tissue observed using scanning electron microscopy - a pilot study

Abstract: Structural changes within the placenta are observed in the course of pathological pregnancy. The aim of the study was to perform initial assessment of morphological features of placenta. The analysis was conducted by Scanning Electron Microscopy. Samples of placenta of women who delivered neonates appropriate for gestational age were characterized by a homogenous surface texture with natural corrugation. The surface of IUGR placenta from the group of mothers with pregnancy induced hypertension was definitely h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 9 publications
1
7
0
1
Order By: Relevance
“…Also, the thickness of the placental barrier might be increased by the deposition of fibrin in the villous core as was demonstrated in the current study and mentioned by many authors [1,21,28,33]. Fibrin deposition has been attributed to an increased placental antifibrinolytic potential.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Also, the thickness of the placental barrier might be increased by the deposition of fibrin in the villous core as was demonstrated in the current study and mentioned by many authors [1,21,28,33]. Fibrin deposition has been attributed to an increased placental antifibrinolytic potential.…”
Section: Discussionsupporting
confidence: 72%
“…In PE, OS causes structural and physiological damage to DNA, RNA and lipids with a significant cellular damage and death. Thus, it could be ruled out that hypoxia of the trophoblast cells, together with reduction of ATP biosynthesis and OS may induce apoptosis of placental cells [12,32,33]. In the same context, accumulation of glycogen in the trophoblasts of PE placentas may be considered a metabolic marker of immaturity, as it was stated that glycogen content tends to decrease as cells reach maturity [14].…”
Section: Discussionmentioning
confidence: 99%
“…67 Thereafter, electron microscopy has been used by other investigators to delineate fine detail in the placental vasculature of monkeys, 68 minks, 69,70 horses, 71 rodents 40,52,59,[72][73][74] and humans. 68,[75][76][77][78][79][80][81][82][83][84][85][86] Demir and colleagues have used TEM to investigate the development of feto-placental villous trees during the early period of ectopic human pregnancy compared to normal pregnancy. 80 A decade later, Coan and colleagues investigated the mouse placental exchange region, which included characterising cytoplasmic bridges attached to several areas of the interhaemal membrane.…”
Section: Electron Microscopymentioning
confidence: 99%
“…40,73,84,88,89 SEM has been utilised to reveal the intricate connectivity of feto-placental vasculature of healthy pregnancies 72,78,79 and complicated pregnancies such as FGR, whereby pronounced variations in placental surface were observed. 72,75 SEM has also been used to provide anatomical comparison between humans and rodents, as well as a deeper understanding of how placental structure associates with fetal outcomes. 40,52,[72][73][74][75][76][77] For example, SEM has revealed that the human placentas of FGR pregnancies exhibit abnormalities in their terminal villi compartments, including reductions in numbers of capillary loops, branches and coiled vessels.…”
Section: Electron Microscopymentioning
confidence: 99%
See 1 more Smart Citation